THE ROLE OF BRAND IMAGE IN MEDIATING THE EFFECT OF PRODUCT QUALITY, SERVICE AND PRICE ON PURCHASE INTEREST - Ajeng Melati, Tri; J. Rachbini, Didik; Rekarti, Endi (Dinasti Publisher, 2021)
The purpose of this study was to analyze the effect of product quality, service and price in influencing purchase intention, as well as to determine the role of brand image mediating the effect of product quality, service and price on purchase interest in the Daihatsu Xenia brand in South Tangerang. The population in this study are people in South Tangerang city who are involved in the process of searching for and purchasing lmpv vehicles. The sample used in this study were 190 respondents. The sampling method was done by using purposive sampling method. This study uses SEM data analysis techniques and data processing using Partial Least Square (PLS). The results of this study indicate that product quality is proven to have a positive and significant effect on brand image, service quality is proven to have a positive and significant effect on brand image, price is proven to have a positive and significant effect on brand image, product quality is not proven to have a positive and significant effect on brand image. Purchase interest, service quality is proven to have a positive but insignificant influence on purchase intention, price is proven to have a positive and significant effect on purchase intention, brand image is proven to have a significant effect on purchase interest. Then in this study it is also proven that brand image fully mediates the relationship of product quality to purchase intention, brand image does not mediate the relationship of service quality to purchase intention, brand image partially mediates the relationship between price and purchase intention.